On Projective Equivalence of Univariate Polynomial Subspaces - Crooks, P.; Milson, R. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We pose and solve the equivalence problem for subspaces of Pn, the (n+1) dimensional vector space of univariate polynomials of degree ≤ n. The group of interest is SL2 acting by projective transformations on the Grassmannian variety GkPn of k-dimensional subspaces. We establish the equivariance of the Wronski map and use this map to reduce the subspace equivalence problem to the equivalence problem for binary forms.